2019
DOI: 10.15171/hpr.2019.24
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology, Therapeutic Patterns, Outcome, and Challenges in Managing Septic Shock in a Sub-Saharan African Intensive Care Unit: A CrossSectional Study

Abstract: Background: Septic shock (SS) is a health priority in sub-Saharan Africa. However, there is a dearth of data in this regard. Objective: This study aimed to determine the epidemiology, therapeutic patterns, outcome, and challenges in managing SS in a tertiary intensive care unit (ICU) of sub-Saharan Africa. Methods: The hospital files of 36 consecutive patients admitted to the ICU of the Douala General Hospital (DGH), Cameroon over the year 2018 were reviewed for SS. SS was diagnosed based on Sepsis-3 defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Patients with blood sodium levels above 150 mmol/L have a mortality rate between 30 and 48 percent, according to some studies carried out on the potential efects of hypernatremia on outcomes in critically sick patients in a medical ICU [26][27][28]. Relating to coma, a study carried out by Bekele et al in Ethiopia and Mbengono et al in Cameroon, reported that patients admitted with a Glasgow coma scale <9 were more likely to die [29,30]. Tis is understandable since a low GCS refects the severity of neurological impairment and reduced patient autonomy, making the patient more dependable and requiring closer monitoring [31].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with blood sodium levels above 150 mmol/L have a mortality rate between 30 and 48 percent, according to some studies carried out on the potential efects of hypernatremia on outcomes in critically sick patients in a medical ICU [26][27][28]. Relating to coma, a study carried out by Bekele et al in Ethiopia and Mbengono et al in Cameroon, reported that patients admitted with a Glasgow coma scale <9 were more likely to die [29,30]. Tis is understandable since a low GCS refects the severity of neurological impairment and reduced patient autonomy, making the patient more dependable and requiring closer monitoring [31].…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of different types of shock varies depending on the population served by the ED (4). Furthermore, shock, particularly septic shock, is reported to account for up to 9.4% of Intensive Care Unit (ICU) admission (5, 6).…”
Section: Introductionmentioning
confidence: 99%
“…It is also one of the major causes of mortality in the emergency room (1,7). Various studies conducted in different clinical settings around the world, including reviews, have shown that the rate of shock-related mortality ranges from 12% to 56.2%, depending on the type of shock (8)(9)(10)(11)(12)(13), the severity of shock (14)(15)(16), and the severity of underlying illness (15,17,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies conducted in Europe, North America, China, and sub-Saharan Africa also demonstrated that patients admitted with a diagnosis of septic shock had a higher likelihood of ICU mortality compared to patients admitted with other diagnoses. [29][30][31] Patients with HIV comorbidity who were admitted to the ICU had an approximately 4.4 times higher risk of ICU mortality compared to patients without HIV comorbidity (AOR = 4.422765, 95% confidence interval: 1.3613-14.368). This strong association could be due to the fact that HIV infection is associated with an increased risk of severe infections, which in turn can contribute to higher ICU mortality rates.…”
mentioning
confidence: 99%